The Association between Eating Rate and Body Mass Index on Sixth Semester Female Medical Students of Sebelas Maret University - Firnanda, Sani Widya; Wiboworini, Budiyanti; Widyaningsih, Vitri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: Many studies reported association between obesity and eating rate. Therefore, decreased eating rate is recommended to manage obesity. This study aims to analyze correlation between eating rate and body mass index. Methods: A quasi experimental study was conducted in a population of female students in the sixth semester of Faculty of Medicine, Sebelas Maret University. Fifty female students were gathered through purposive sampling methods with age 18 through 23 years old and body mass index â¥18.5. Eating rate was measured twice at breakfast with chicken noodle (521.7 kkal) and soto (233 kkal) on different day. Subjects were asked to eat in their normal pace and their eating rate were measured by stopwatch at the same time. Body mass index was measured by anthropometry. Statistical analysis was performed using simple linear regression. Results: Statistical analysis showed that there was significant association between eating rate and body mass index (p < 0.001) for both chicken noodle and soto. Simple linear regression indicated that higher eating rate was associated with higher body mass index and vice versa. The linear regression equation for chicken noodle was Body Mass Index = 34.837 â 1.577 (Eating Rate of Chicken Noodle) and the equation for soto was Body Mass Index = 36.696 â 1.837 (Eating Rate of Soto). Conclusions: There was significant association between eating rate and body mass index of female students in the sixth semester of Faculty of Medicine, Sebelas Maret University. Keywords: eating rate, satiety level, body mass index